Time management skills (Rugeley : Focus Multimedia Limited, 2005)
A multimedia course, using audio video clips and video examples, that assists you in assessing how you currently use your time and shows you the best methods to prioritise your workload, avoid time wasting, and take control of your schedule.
Ελάχιστες απαιτήσεις συστήματος: IBM compatible PC; Pentium 133 processor or equivalent; 32 MB RAM; Windows 98 or later; 80 MB of free hard disk space.
Keywords: CD-ROMs.; Time management -- CD-ROMs.